PENGARUH PERSONAL COST, KOMITMEN ORGANISASI, SENSITIVITAS ETIS DAN MACHIAVELLIAN TERHADAP MINAT MELAKUKAN WHISTLEBLOWING PADA ORGANISASI PERANGKAT DAERAH KABUPATEN GIANYAR - Dewa Ayu Riska Ari Dewi; Sang Ayu Putu Arie Indraswarawati (UNHI Press, 2020)
Whistleblowingj is thej disclosure ofj violationsj or unlawful acts, reportingj by an employee or one ofj thej members ofj thej organizationj (active or non-active) regardingj violations, which may be able to influence them inj thej act ofj committingj a violation. Thej purpose ofj this study was to determine thej effect ofj personalj costj, organizational commitment, ethical sensitivity and Machiavellianj to thej interest inj whistleblowingj inj thej regional apparatus organizationj inj Gianyarj. This research was carried out inj thej Gianyarj district apparatus organizationj usingj a questionnaire technique as a dataj collectionj method. Thej number ofj samples used was 92 respondenjts usingj a nonprobality samplingj method with a purposive samplingj technique and thatj met thej sample selectionj criteria. Dataj analysis techniques usingj multiple linear regressionj analysis. Based onj thej results ofj thej analysis show thatj personalj costj and organizational commitment does not significantly influence thej interest inj doingj whistleblowingj, while ethical sensitivity and Machiavellianj have a positive and significant effect onj thej interest inj doingj whistleblowingj.